Endothelial cells' biophysical, biochemical, and chromosomal aberrancies in high‐glucose condition within the diabetic range. (17th February 2017) - Rezabakhsh, Aysa; Nabat, Elahe; Yousefi, Mina; Montazersaheb, Soheila; Cheraghi, Omid; Mehdizadeh, Amir; Fathi, Farzaneh; Movassaghpour, Ali Akbar; Maleki‐Dizaji, Nasrin; Rahbarghazi, Reza; Garjani, Alireza
Abstract : To date, many studies have been conducted to find out the underlying mechanisms of hyperglycemia‐induced complications in diabetes mellitus, attributed to the cellular pathologies of different cells—especially endothelial cells. However, there are still many ambiguities and unresolved issues to be clarified. Here, we investigated the alteration in biophysical and biochemical properties in human umbilical vein endothelial cells exposed to a high‐glucose concentration (30mM), comparable to glucose content in type 2 diabetes mellitus, over a course of 120 hours. In addition to a reduction in the rate of cell viability and induction of oxidative stress orchestrated by the high‐glucose condition, the dynamic of the fatty acid profile—including polyunsaturated, monounsaturated, and saturated fatty acids—was also altered in favor of saturated fatty acids. Genetic imbalances were also detected at chromosomal level in the cells exposed to the abnormal concentration of glucose after 120 hours. Moreover, the number of tip cells (CD31 + /CD34 + ) and in vitro tubulogenesis capability negatively diminished in comparison to parallel control groups. We found that diabetic hyperglycemia was associated with a decrease in the cell‐cell tight junction and upregulation in vascular endothelial cadherin and zonula occludens (ZO)‐1 molecules after 72 and 120 hours of exposure to the abnormal glucose concentration, which resulted in a profound reduction in transendothelial electrical resistance. The surface plasmon resonance analysis of the human umbilical vein endothelial cells immobilized on gold‐coated sensor chips confirmed the loosening of the cell to cell intercellular junction as well as stable attachment of each cell to the basal surface. Our findings highlighted the disturbing effects of a diabetic hyperglycemia on either biochemical or biophysical properties of endothelial cells.